1991
DOI: 10.5980/jpnjurol1989.82.1594
|View full text |Cite
|
Sign up to set email alerts
|

Serious Complications of Intravesical Bacillus Calmette-Guerin Therapy in Patients With Bladder Cancer

Abstract: Side effects and serious complications of intravesical bacillus Calmette-Guérin (BCG) therapy were reviewed in 120 patients with transitional cell carcinoma of the urinary bladder from October, 1983 to June, 1989 at Hirosaki University Hospital. As local side effects, 102 patients (85.0%) had bladder irritability with frequency and/or micturition pain, and 46 patients (38.3%) had hematopyuria. As systemic side effects, fever in 43 patients (35.8%), elevation of serum GOT, GPT in 9 patients (7.5%), and malaise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

1993
1993
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…(colony-forming units)/mg] than other strains (13), indicating that equipotent efficacy can be attained even at half of its standard dose (8). On the other hand, we should pay attention to the frequent occurrence of harmful events related to BCG (6), which urges us to reduce the possible complications. By referring to the previous clinical data obtained by BCG instillation at a standard dose (80 mg), we investigated the treatment outcomes in our patients given a lower dose (40 mg) of BCG, attempting to…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(colony-forming units)/mg] than other strains (13), indicating that equipotent efficacy can be attained even at half of its standard dose (8). On the other hand, we should pay attention to the frequent occurrence of harmful events related to BCG (6), which urges us to reduce the possible complications. By referring to the previous clinical data obtained by BCG instillation at a standard dose (80 mg), we investigated the treatment outcomes in our patients given a lower dose (40 mg) of BCG, attempting to…”
Section: Discussionmentioning
confidence: 99%
“…Akaza et al (5) observed bladder irritation symptoms in 69%, fever in 43.7% and macroscopic hematuria in 31%. Infrequent but severe adverse effects have also been reported (6), making it necessary to define the optimal BCG instillation method to improve safety while maintaining its efficacy. Although assessment criteria for adverse effects vary among reports, the incidence of local symptoms in the bladder (bladder irritation symptoms, hematuria and pyuria) in this study turned out to be similar to those in previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cause of the contracted bladder after BCG instillation remains unclear. However, it has been suggested that severe inflammatory reactions that persist over the long‐term 5 low bladder capacity after partial cystectomy or frequent TURBT, and many BCG instillations 2 may be possible factors associated with contracted bladder. Nagayama et al 6 .…”
Section: Discussionmentioning
confidence: 99%
“…Contracted bladder is a rare but severe adverse event after intravesical BCG instillation, with an incidence of 0.2–3.3%. 1 , 2 , 3 Conservative treatment with antituberculosis drugs, steroids, and bladder hydrodistension is the first treatment option for contracted bladder. However, cystectomy can be performed in cases in which conservative treatment achieved no improvement.…”
Section: Introductionmentioning
confidence: 99%